Assembly, annotation, and comparative whole genome sequence of fusarium verticillioides isolated from stored maize grains - Navale, Vishwambar D.; Sawant, Amol M.; Gowda, Varun U.; Vamkudoth, Koteswara Rao (2022)
Fusarium verticillioides is a plant pathogenic fungus affecting a wide range of crops worldwide due to its toxigenic properties. F. verticillioides BIONCL4 strain was isolated from stored maize grain samples in India, and produces high amount of fumonisin B1 (FB1). We report a comparative genomic analysis of F. verticillioides, covering the basic genome information, secretome, and proteins involved in host-pathogen interactions and mycotoxin biosynthesis. Whole-genome sequencing (WGS) was performed using the Illumina platform with an assembly size of 42.91 Mb, GC content of 48.24%, and 98.50% coverage with the reference genome (GCA000149555). It encodes 15,053 proteins, including 2058 secretory proteins, 676 classical secretory proteins, and 569 virulence and pathogenicity-related proteins. There were also 1447 genes linked to carbohydrate active enzymes (CaZymes) and 167 genes related to mycotoxin production. Furthermore, F. verticillioides genome comparison revealed information about the species' evolutionary history. The overall study helps in disease prevention and management of mycotoxins to ensure food safety.
Keywords: comparative genomics; Fusarium verticillioides; mycotoxin biosynthesis; plant-pathogen interaction; Secretome; whole-genome sequencing